COMPARATIVE EKONOMI SISTEM DAN PRAKTEK NEO-LIBERAL DALAM PEREKONOMIAN INDONESIA - Dinarjad Achmad, . (Fakultas Ekonomi dan Bisnis, UNTAN, 2010)
ABSTRACT The main aims of this paper are to highlight theoretically and empirically three competing different economic systems prevailing throughout the world with the main emphasis on the capitalistic system (neo liberal) and its pervasive practice in Indonesia economy. Theoritically, the economic system consists of capitalistic system and socialistic system, but no country has been found to practice purely both systems. Most people claim that Indonesian economy as an Indonesia-specific system what so-called Pancasila economic system, but many people regard it as capitalistic system represented by free market economic policy (neo-liberal). The phenomenon of neo liberal practice in Indonesia economy has been in existence since Suharto’s new order administration, during which foreign loans was highly predominant in the economic development financing in Indonesia, mainly from the world Bank and the IMF with their structural adjustment program. But, neo liberal might appear to have been failed as proven by the breakout of deep monetary crisis in Indonesia in 1997. Keywords: Sistem ekonomi Kapitalis, Sosialis dan Neo-liberal